Discourse Markers in the Introductory Section of Research Articles in National accredited Journal - Fadilla, Hilda; Widhiyanto; Wahyuni , Sri (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
Discourse markers provide writers with signaling devices to connect ideas and guide readers in grasping the connection of ideas in the texts. An introductory section of a journal article represents a unique text which should be written with clear and interconnected arguments. This paper aims to reveal how discourse markers play vital roles in realizing the development of the arguments in this knotty text. To achieve this, introductory sections of articles published in a nationally accredited journal were examined. Using Fraser's (2009) functional classes of discourse markers, 22 introduction sections were analyzed employing text analysis to determine the usage of these markers. It was found that despite employing all types of discourse markers, not all of them were applied appropriately. Their uses may not be in line with their functional classification. Among others, there are three functional classes of discourse markers proposed by Fraser (2009), they are contrastive markers, elaborative markers, and inferential markers. Elaborative markers were the most used type among the different types, followed by contrastive and inferential markers. This implies that authors tended to develop ideas more often, whereas contrastive and inferential markers were used less frequently but were crucial for indicating differences and making conclusions within the texts.